(untitled) (Medicine Today, 2012)
Genital herpes clinically underestimated because symptoms or sign occur only in some infection detected serologically. Prevalence of HSV subtypes in microbial etiology of Genital Ulcer Disease (GUD) in men, their association with clinical sign, complex of GUD and high-risk behavior were assessed. One hundred men with first episodes of genital ulcers were prospectively studied for serological evidence of syphilis (RPR and TPHA; T.pallidum IgM and IgG antibodies) and Polymerase Chain Reaction (PCR) proven chancroid and herpes. Demographic and epidemiological data were obtained in a standard interview. Positive syphilis serology observed in 11 cases, H. ducreyi detected in 65 cases and Herpes Simplex Virus in 13 cases. Among the PCR proven infections HSV type-2 detected in 7 cases, HSV type-1 in 4 cases and both HSV type-1 & 2 in 2 cases. Most of the HSV infections (92.3%) found as mixed infection with H. ducreyi. There was one PCR detected genital herpes case that was clinically undetermined. Among the PCR proven HSV infections clinical sign complex of genital herpes observed in one case, which had mixed microbial etiology. HSV infection was more prevalent in married than unmarried men (25.0% vs. 8.3%; P<0.05) and associated with early age promiscuous activity, multiple sexual partner, and sex with commercial sex workers and past infection with STDs. Presence of underdiagnosed HSV infection in men with GUD stress on the need for clinical suspicion of multiple infections. Patient with GUD should be carefully evaluated for HSV infection. Medicine Today 2010 Volume 22 Number 02 Page 55-61 DOI: http://dx.doi.org/10.3329/medtoday.v22i2.12430